Archaeological Research on the Ancient City Site of Akra in Eastern Crimea - Solovyev, Sergey; Vakhoneev, Viktor (Hyperboreus, 2024)
The article is devoted to the latest archaeological research on the ancient settlement of Akra on a sandy embankment near the village of Zavetnoye in eastern Crimea. This ancient settlement was localized only in the early 1980s, and the history of its study has 3 stages. The authors analyze the reasons why the cultural layer was preserved underwater and was not destroyed by surf waves as on other coastal archaeological sites. Special attention is paid to the topography and layout of the monument in the Hellenistic and Roman periods. The settlement is divided into two very different research sites: underwater and terrestrial. The underwater part accounts for about 70 % of the monument’s territory. It was preserved due to the presence of a powerful defensive wall built in the 4th century BC. Cultural layers under water were preserved only in areas close to this wall. The Hellenistic urban development of Akra included residential houses of the typical planning scheme, arranged in city blocks. At least six building complexes from this time were studied there. Unfortunately, the layers from Roman times have not been preserved underwater, while on a small piece of land, areas of dense buildings from the first centuries AD have recently been discovered. Finally, the latest research has also confirmed the presence of life in the settlement in the early medieval period.